1991
DOI: 10.1093/jac/28.5.707
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combinations of cefotiam and other antibiotics on methicillin-resistant Staphylococcus aureus in vitro

Abstract: The in-vitro activities of cefmetazole, flomoxef, imipenem, vancomycin and enramycin alone and in combination with cefotiam against eighteen clinically isolated methicillin-resistant Staphylococcus aureus was investigated. Cefotiam, cefmetazole, flomoxef and imipenem inhibited the growth of clinical isolates at concentrations ranging from 100 to 1600, 6.25 to 400, 6.25 to 400 and 0.78 to 200 mg/L, respectively. Synergic effects were observed with combinations of cefotiam and cefmetazole, flomoxef or imipenem a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results of our bitherapies compared favorably with those of previous works evaluating the killing activity of combinations of vancomycin and either cefotiam (35) or cefpirome (29) against MRSA: for the cefotiam-vancomycin combination, only a weak synergistic bacteriostatic effect was reported; for the cefpirome-vancomycin regimen, the bactericidal effect at 24 h was observed only against the two strains homogeneously resistant to methicillin. In a previous work performed with a single MRSA strain (36), the bactericidal effect of the imipenemvancomycin combination has been reported to be dependent on the imipenem concentration.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results of our bitherapies compared favorably with those of previous works evaluating the killing activity of combinations of vancomycin and either cefotiam (35) or cefpirome (29) against MRSA: for the cefotiam-vancomycin combination, only a weak synergistic bacteriostatic effect was reported; for the cefpirome-vancomycin regimen, the bactericidal effect at 24 h was observed only against the two strains homogeneously resistant to methicillin. In a previous work performed with a single MRSA strain (36), the bactericidal effect of the imipenemvancomycin combination has been reported to be dependent on the imipenem concentration.…”
Section: Discussionsupporting
confidence: 75%
“…It is noteworthy that the imipenem-vancomycin regimen produced the best results, in terms of both FIC values and the antibiotic concentrations generating bacteriostatic synergy. By checkerboard studies, synergistic bacteriostatic effects of ␤-lactam-vancomycin combinations against MRSA have been previously reported for imipenem and cephalosporins such as cefotiam, cefoperazone, and cefpirome (3,9,30,35,36), but not for oxacillin (8). However, unlike our results, the synergistic FIC values usually observed in such studies were frequently high, close to the 0.5 limit value for synergy (9,30).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many contradictory observations with regard to the combination effect of vancomycin and ␤-lactam against S. aureus clinical isolates, including additive and/or synergistic effects (2,4,15,18,19,20,21) and antagonistic effects (7, 9, 14; H. Hanaki, S. Ohkawa, Y. Inaba, T. Hashimoto, and K. Hiramatsu, Abstr. 38th Intersci.…”
mentioning
confidence: 99%
“…Several recent studies from Japan have shown that combinations of carbapenems with ␤-lactams and cephalosporins with penicillins exhibit synergy against MRSA (13)(14)(15). As far as is known, MRSA is resistant to ␤-lactams because of the presence of an altered penicillin-binding protein (PBP 2a) with reduced affinity for methicillin and other ␤-lactam antibiotics (4,9).…”
mentioning
confidence: 99%